The prevention of torture : an ecological approach / Danielle Celermajer. - Celermajer, Danielle (Cambridge University Press, 2018)
There is an urgent need to analyze and assess how we prevent torture, against the background of a rigorous analysis of the factors that condition and sustain it. Drawing on rich empirical material from Sri Lanka and Nepal, The Prevention of Torture: An Ecological Approach interrogates the worlds that produce torture, in order to propose how to bring about systemic institutional and cultural change. Critics have decried human rights approaches' failure to attend to structural factors, but this book seeks to go beyond a 'stance of criticism' to take up the positive project of reimagining human rights theory and practice. It discusses key debates in human rights and political theory, as well as the challenges that advocates face in translating situational analyses into real world interventions. Danielle Celermajer develops a new, ecological framework for mapping the worlds that produce torture, and thereby develops prevention strategies.